2022
DOI: 10.1038/s41413-022-00203-2
|View full text |Cite
|
Sign up to set email alerts
|

Versatile subtypes of pericytes and their roles in spinal cord injury repair, bone development and repair

Abstract: Vascular regeneration is a challenging topic in tissue repair. As one of the important components of the neurovascular unit (NVU), pericytes play an essential role in the maintenance of the vascular network of the spinal cord. To date, subtypes of pericytes have been identified by various markers, namely the PDGFR-β, Desmin, CD146, and NG2, each of which is involved with spinal cord injury (SCI) repair. In addition, pericytes may act as a stem cell source that is important for bone development and regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 151 publications
0
30
0
Order By: Relevance
“…Recent studies have uncovered a subtype of perivascular cells whose markers include platelet-derived growth factor receptor beta (Pdgfrβ) and NG2. These perivascular cells exhibit mesenchymal stem-cell properties and are involved in spinal cord injury repair (Zhu et al 2022). Nevertheless, NG2 glia are also characterized by Pdgfrα expression (reviewed in (Nishiyama et al 2016)), and therefore we used immunodetection of Pdgfrα to distinguish these cells from NG2 + perivascular cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have uncovered a subtype of perivascular cells whose markers include platelet-derived growth factor receptor beta (Pdgfrβ) and NG2. These perivascular cells exhibit mesenchymal stem-cell properties and are involved in spinal cord injury repair (Zhu et al 2022). Nevertheless, NG2 glia are also characterized by Pdgfrα expression (reviewed in (Nishiyama et al 2016)), and therefore we used immunodetection of Pdgfrα to distinguish these cells from NG2 + perivascular cells.…”
Section: Resultsmentioning
confidence: 99%
“…Type A pericytes are abluminal to Type B pericytes, with Type B expressing desmin and αSMA in addition to other pericyte markers [ 44 ]. Despite these observations and many other studies regarding different subtypes of pericytes [ 89 ], a recent scRNA-seq study did not identify pericytes subtypes in mouse brain vasculature [ 65 ]. However, two distinct subtypes have been identified in the human brain by scRNA-seq [ 74 ].…”
Section: The Cellular Origins Of Fibroblasts In the Fibrotic Scarmentioning
confidence: 91%
“…Pericytes are involved in the establishment of the blood-brain barrier and the blood-spinal cord barrier, as well as the stability of the internal environment of the brain and spinal cord (Cheng et al, 2018;Sweeney et al, 2019). Previous studies have shown that pericytes are closely related to the formation of scars and the recovery of function after SCI (Dias et al, 2018;Hesp et al, 2018;Zhu et al, 2022). Some studies have confirmed that m6A modification in pericytes is involved in the occurrence and development of hypertension and diabetes (Wu Q. et al, 2019;Suo et al, 2022).…”
Section: N6-methyladenosine Modification and Scarring After Spinal Co...mentioning
confidence: 99%